2021
DOI: 10.3389/fmars.2021.743836
|View full text |Cite
|
Sign up to set email alerts
|

Resource Status and Effect of Long-Term Stock Enhancement of Large Yellow Croaker in China

Abstract: The large yellow croaker, Larimichthys crocea, was once the most abundant and economically important marine fish in China. Thus far, it has also been the most successful mariculture fish species in China. However, its wild stock severely declined in the 1970s because of overexploitation, and therefore hatchery release has been carried out for stock enhancement since 2000. As a migratory fish, large yellow croaker was divided into three geographical stocks according to ambiguous morphological and biological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…The results suggested that neither genetic drift nor gene flow from allopatric populations had strongly altered the genetic composition of stocks in the East China Sea over this time-span. Consistent with our results, a recent genetic study with three molecular markers also detected relatively high genetic diversity in wild populations of large yellow croaker, which was comparable to those of othermarine fishes (Yuan et al, 2021). Our result was also consistent with previous results of temporal genetic analysis in Atlantic salmon, Brown trout, North Sea sole and Copper redhorse, which also documented temporal stability of genetic diversity over decades of overexploitation (Hansen et al, 2002;Lippe et al, 2006;Cuveliers et al, 2011;Pinsky et al, 2021).…”
Section: Absence Of Temporal Depletion Of Genetic Diversitysupporting
confidence: 93%
See 2 more Smart Citations
“…The results suggested that neither genetic drift nor gene flow from allopatric populations had strongly altered the genetic composition of stocks in the East China Sea over this time-span. Consistent with our results, a recent genetic study with three molecular markers also detected relatively high genetic diversity in wild populations of large yellow croaker, which was comparable to those of othermarine fishes (Yuan et al, 2021). Our result was also consistent with previous results of temporal genetic analysis in Atlantic salmon, Brown trout, North Sea sole and Copper redhorse, which also documented temporal stability of genetic diversity over decades of overexploitation (Hansen et al, 2002;Lippe et al, 2006;Cuveliers et al, 2011;Pinsky et al, 2021).…”
Section: Absence Of Temporal Depletion Of Genetic Diversitysupporting
confidence: 93%
“…Sporadic genetic differentiation among temporal samples might occur due to random genetic drift or technical errors. To a large extent, these results were in accordance with previous studies on populaiton genetic structure of large yellow croaker in which a single panmictic population were suggested across its distribution (Han et al, 2015;Yuan et al, 2021). Our results indicated that the population genetic structure of large yellow croaker was generally spatio-temporal stable and had not been changed substantially due to the fishing pressure.…”
Section: Evidence For Stable Spatio-temporal Genetic Structuresupporting
confidence: 92%
See 1 more Smart Citation
“…We selected ten fish species with accumulated sample sizes larger than 30 individuals as representatives of the most abundant fish in Sansha Bay (Supplementary Table S1). One of the species, Larimichthys crocea, is not representative of wild populations but farmed resulting from long-term (since 2002), restocking activities in Sansha Bay after the natural populations were depleted in the 1980s (Liu and Sadovy de Mitcheson, 2008;Liu et al, 2020;Yuan et al, 2021), and it was taken as a negative control (i.e. expected low genetic diversity) in the evaluation of the other fish species.…”
Section: Sampling and Species Identificationmentioning
confidence: 99%
“…It is rich in protein and fat as well as essential amino acids and polyunsaturated fatty acids. Large yellow croaker resources are very abundant in China [ 2 ]. In 2020, the seawater aquaculture production of the large yellow croakers had reached 21,353,100 tons in China.…”
Section: Introductionmentioning
confidence: 99%